A Analisis Penggunaan Bahasa Empatik dalam Pemberitaan Bencana Alam di Media Online Aceh - Nurafandi, Naswa; Safriandi; Wulanda (Global Action and Education for Society, 2026)
This study aims to analyze the use of empathetic language in natural disaster reporting in Aceh online media. The background of this research is based on the importance of language as a means of building social empathy and psychological support for disaster victims through reporting. Empathetic language is understood as a form of communication that reflects concern for the feelings and experiences of others, especially in crisis situations. This study employs a descriptive qualitative approach with data collection techniques involving reading and noting 25 news articles from 13 online media outlets in Aceh, namely Serambi Indonesia, AJNN.net, KBA. ONE, Harian Rakyat Aceh, Aceh Info, Haba Nusantara.net, Waspada Aceh.com, Noa.co.id, Koalisi.co, Aceh.tribunnews.com, Portalsatu.com, Anteroaceh.com, and Acehkini.id published between 2023 and 2024. Data analysis was conducted based on Davis' empathetic theory, which encompasses four aspects: perspective taking, empathic concern, personal distress, and fantasy. The research findings revealed 64 instances of empathetic language, comprising 48 instances of empathic concern, 9 instances of perspective taking, and 7 instances of personal distress. The fantasy aspect was not identified as the news texts were factual and objective in nature. The novelty of this study lies in its focus on linguistically analyzing the use of empathetic language in the context of disaster journalism in the Aceh region, as well as the application of Davis' theory, which has not been widely used in journalistic language studies. This study contributes to the development of empathetic communication in the mass media and encourages more humanistic journalistic practices.